Micro-geographical heterogeneity in Schistosoma mansoni and S. haematobium infection and morbidity in a co-endemic community in northern Senegal. - Lynn Meurs; Moustapha Mbow; Nele Boon; Frederik van den Broeck; Kim Vereecken; Tandakha Ndiaye Dièye; Emmanuel Abatih; Tine Huyse; Souleymane Mboup; Katja Polman (Public Library of Science (PLoS), 2013)
BACKGROUND: Schistosoma mansoni and S. haematobium are co-endemic in many areas in Africa. Yet, little is known about the micro-geographical distribution of these two infections or associated disease within such foci. Such knowledge could give important insights into the drivers of infection and disease and as such better tailor schistosomiasis control and elimination efforts. METHODOLOGY: In a co-endemic farming community in northern Senegal (346 children (0-19 y) and 253 adults (20-85 y); n = 599 in total), we studied the spatial distribution of S. mansoni and S. haematobium single and mixed infections (by microscopy), S. mansoni-specific hepatic fibrosis, S. haematobium-specific urinary tract morbidity (by ultrasound) and water contact behavior (by questionnaire). The Kulldorff's scan statistic was used to detect spatial clusters of infection and morbidity, adjusted for the spatial distribution of gender and age. PRINCIPAL FINDINGS: Schistosoma mansoni and S. haematobium infection densities clustered in different sections of the community (p = 0.002 and p = 0.023, respectively), possibly related to heterogeneities in the use of different water contact sites. While the distribution of urinary tract morbidity was homogeneous, a strong geospatial cluster was found for severe hepatic fibrosis (p = 0.001). Particularly those people living adjacent to the most frequently used water contact site were more at risk for more advanced morbidity (RR = 6.3; p = 0.043). CONCLUSIONS/SIGNIFICANCE: Schistosoma infection and associated disease showed important micro-geographical heterogeneities with divergent patterns for S. mansoni and S. haematobium in this Senegalese community. Further in depth investigations are needed to confirm and explain our observations. The present study indicates that local geospatial patterns should be taken into account in both research and control of schistosomiasis. The observed extreme focality of schistosomiasis even at community level, suggests that current strategies may not suffice to move from morbidity control to elimination of schistosomiasis, and calls for less uniform measures at a finer scale.